Bringing in the citizen: Stakeholder participation in co-production processes of sustainable housing - Ahtosalo, Hanna; Harju, Charlotta; Kylkilahti, Eliisa; Lukkarinen, Jani; Lähtinen, Katja; Syrjälä, Henna (Springer, 2026)
Incorporating citizen views through stakeholder engagement enhances the democratic and equitable governance of sustainability transitions. Using stakeholder theory as a conceptual frame, this study evaluates the use of different stakeholder participation processes to co-produce solutions for more sustainable housing in Finland. This study examines how citizens are positioned, levels of participation, and factors affecting success. Data were collected in three participatory processes: a service design process, a hackathon, and transition arenas, which sought to improve citizens’ opportunities for more sustainable housing. Our results show that citizens were positioned differently across the stakeholder processes. Although all processes aimed for high levels of participation—such as collaboration and empowerment—the achieved levels varied and, in some cases, remained limited. Moreover, several contextual, organizational, and process-related factors influenced the outcomes and shaped how participating stakeholders perceived citizens’ views. Addressing these challenges is crucial when selecting participatory methods for research, planning, and policy.
Keywords: Citizen participation; Co-production; Hackathon; Participatory processes; Service design; Transition arena; fi=Markkinointi|en=Marketing|